Soft Tissue Cephalometric Measurements Among Malaysian Malays and Chinese - Nor Farid Mohd Noor; Rehana Basri; Mohammad Khursheed Alam; Sanjida Haque; Melvin Saw Jian Hao; Maisarah Abu Talib (Association of Support to Oral Health Research (APESB), 2022)
Objective: To obtain the standardized values of individuals of Malaysian Malay and Chinese for further relevant research, such as treatment planning and aesthetical considerations. Material and Methods: In this retrospective study, 440 (305 were Malays and 135 were Chinese) standardized lateral cephalometric radiographs of orthodontic patients selected through simple random sampling are profiled using Holdaway's analysis. The independent t-test was used to assess the disparities in race and gender. The significant level was p<0.05. Results: Significant differences were found between the Malays and Chinese in their skeletal profile convexity, superior sulcus depth, inferior sulcus to the H line and nose prominence. Between Malay females and males, there are significant differences in superior sulcus depth, soft tissue subnasale to H line, basic upper lip thickness, upper lip thickness and nose prominence. Between Chinese males and females, there were differences in their skeletal profile convexity, upper lip to H line, basic upper lip thickness and upper lip thickness. Conclusion: The findings demonstrated the difference between standardized norms and the unique profiles of Malaysian Malays and Chinese. There are significant gender disparities in the soft tissue cephalometric measurements among Malaysian Malay and Chinese subjects.